Penelitian untuk rol karet gilingan padi - Herminiwati Herminiwati; Arum Yuniari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1987)
8 (eight) samples of different trade-mark of Rice hulling rubber rolls that consist of four types of roll size, the colour of which are grey, dark green and brown are tested for the purpose of this research. The roll testing method and technical specification is taken from Indian Standard and Japanese Industrial Standard. The test results of physical properties which are determinated as the decisive factor of the quality are as follow : thickness 18,54 mm – 21,60 mm, tensile strength 10,85 N/mm2 – 16,65 N/mm2 , elongation at break 106,8 % - 258,0 %, hardness before anging 87 – 95 Shore A and after aging 82 – 92 Shore A, abrasion resistance (Grasselli) 0,070 mm3/kgm – 0,79 mm3/kgm